Environmental politics in controlling land and forest fires - Elyta, Elyta; Afhiani, Syarifah Nurma; Siringo, Tulus Gover (The International Journal of Politics and Sociology Research, 2024)
Environmental Politics advocates for a collaborative approach among government, industry, academics, and civil society to address Indonesia's complex forest and land fire challenges. The government is pivotal in policy initiation and regulation, requiring effective prevention and response strategies. Industry contributes through technological innovation, particularly in fire risk monitoring and mitigation. Academia offers scientific research to build sustainable forest and land management strategies. As supervisors and stakeholders, civil society can actively participate in environmental management. Close collaboration among these sectors is essential, with the government leading coordination efforts, industry providing technology, academia offering scientific insight, and civil society engaging in education and community empowerment. Building community capacity in forest management and environmental monitoring is crucial. This collaborative effort aims to create synergy in tackling forest and land fires, emphasizing sustainable resource management, monitoring illegal activities, and promoting responsible environmental practices. Implementing Environmental Politics in Indonesia highlights a shared commitment to environmental sustainability and national sovereignty amidst globalization and climate change.